Comparing patient dissatisfaction and rational judgment in intentional medication non‐adherence versus unintentional non‐adherence. (25th September 2013) - Iihara, N.; Nishio, T.; Okura, M.; Anzai, H.; Kagawa, M.; Houchi, H.; Kirino, Y.
Summary What is known and objective Patients' poor adherence to medications is reported to be related to the individual patients' beliefs and cognitions and their trust of the medical staff. However, the causes of the two forms of non‐adherence, intentional and unintentional behaviours, have yet to be clarified. This study compared psychological latent factors associated with intentional and unintentional non‐adherence to chronic medication regimens, focusing on the potential effects of (i) patients' dissatisfaction with treatment and their relationships with the medical staff and (ii) patients' subliminal rational thinking processes, which weighed the positive values such as their expectations of benefits from treatment against negative values such as their dissatisfaction. Methods Two cross‐sectional surveys were undertaken of patients given medications for chronic diseases, using a questionnaire developed and validated in this study. One survey was undertaken in three hospitals and the other survey, online throughout Japan. We scored the individual latent factors using the questionnaire and calculated the differential score between two negatively correlated latent factors to quantify patients' subliminal rational thinking process. We compared the adjusted odds ratio (OR) of latent factors between intentional and unintentional non‐adherence to medication in both surveys. Results and discussion Of the eligible subjects, 149 hospitalized patients and 524 survey participants completed the questionnaire. Intentional non‐adherence was associated with patient dissatisfaction with treatment including interpersonal relationships with medical staff in both hospitalized patients and online survey participants (95% confidence interval of adjusted OR for Dissatisfaction, 1·20–16·26 in the hospital‐based survey and 1·33–3·45 in the online survey). In both surveys, intentional non‐adherence was significantly associated with the differential score between two negatively correlated latent factors, Willingness and Dissatisfaction (P = 0·02 in the hospital‐based survey and P < 0·001 in the online survey). However, these associations were not evident in unintentionally non‐adherent patients. What is new and conclusions Patients' dissatisfaction and their resulting rational judgments are unique, consistent determinants of intentional non‐adherence to medications, but not of unintentional non‐adherence.